A relativistic model of electron cyclotron current drive efficiency in tokamak plasmas - Lin-Liu Y.R.; Hu Y.J.; Hu Y.M. (EPJ Web of Conferences, 2012)
A fully relativistic model of electron cyclotron current drive (ECCD) efficiency based on the adjoint function techniques is considered. Numerical calculations of the current drive efficiency in a tokamak by using the variational approach are performed. A fully relativistic extension of the variational principle with the modified basis functions for the Spitzer function with momentum conservation in the electron-electron collision is described in general tokamak geometry. The model developed has generalized that of Marushchenko’s (N.B . Marushchenko, et al. Fusion Sci. & Tech., 2009), which is extended for arbitrary temperatures and covers exactly the asymptotic for u ≫ 1 when Z → ∞, and suitable for ray-tracing calculations.